2015
DOI: 10.5301/ijao.5000430
|View full text |Cite
|
Sign up to set email alerts
|

Debridement, Antibiotics, Irrigation, and Retention (DAIR) of the Prosthesis after Hip Hemiarthroplasty Infections. Does it Work?

Abstract: Our results indicated limited success to DAIR- treated patients with infected HA. The high failure rate of DAIR treatment after 2 weeks from the implantation should be taken into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Blomfeldt et al [33] reported unfavorable outcomes in hip fracture patients with 82% conversion to excision arthroplasty. Kazimoglu et al [34] reported a DAIR treatment success rate of 41% in a multicenter retrospective study of 39 patients, and similarly, Guren et al [10] reported a success rate of 43% in a singlecenter retrospective study of 35 patients. Additionally, studies have reported increased failure rates arthroplasty for hip fracture compared with elective arthroplasty; Bergkvist et al [21] reported 35% increased failure rate, De Vries et al [35], 23%, and Del Toro et al [36], 21%.…”
Section: Discussionmentioning
confidence: 91%
“…Blomfeldt et al [33] reported unfavorable outcomes in hip fracture patients with 82% conversion to excision arthroplasty. Kazimoglu et al [34] reported a DAIR treatment success rate of 41% in a multicenter retrospective study of 39 patients, and similarly, Guren et al [10] reported a success rate of 43% in a singlecenter retrospective study of 35 patients. Additionally, studies have reported increased failure rates arthroplasty for hip fracture compared with elective arthroplasty; Bergkvist et al [21] reported 35% increased failure rate, De Vries et al [35], 23%, and Del Toro et al [36], 21%.…”
Section: Discussionmentioning
confidence: 91%
“…In a recent study, Kazimoglou et al [15] reported a limited success rate (41%) for the DAIR procedure for the treatment of seven patients with early-onset hemiarthroplasty infections caused by either gram-positive or gram-negative bacteria. They also found that successful outcomes are positively correlated with a duration of the infection after implantation under two weeks and a sedimentation value lower than 60 mm/h.…”
Section: Discussionmentioning
confidence: 99%
“…However, the success in controlling the infection varies from 31% to 100%. 13,[14][15][16][17] Although the term DAIR is not used in megaprosthesis infection papers, the outcome of debridement and implant retention in this group of patients has been very poor. Jeys et al reported that there were 68 patients of 136 patients treated with local debridement.…”
Section: Discussionmentioning
confidence: 99%
“…We left the cartilage untouched as in Kazimoglu et al's report. 15 We deliberately changed the bipolar hip component into a total hip component in order to leave a big piece of 6…”
Section: Discussionmentioning
confidence: 99%